1988
DOI: 10.1042/bj2550977
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phosphatidate bilayers on pig heart AMP deaminase. Crucial role of pH-dependent lipid-phase transition

Abstract: Phosphatidate bilayers composed of dilauroylphosphatidate, dimyristoylphosphatidate, dipalmitoylphosphatidate and dioleoylphosphatidate were prepared. Their interaction with AMP deaminase isolated from pig heart was investigated. Dioleoylphosphatidate bilayers were found to exert non-competitive inhibition on the AMP deaminase with a K1 of 15 x 10-6 M. This inhibition is three orders of magnitude stronger than that exerted by orthophosphate. The phosphatidate species containing saturated fatty acids were eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The interaction was observed with egg‐PC but not with DPPC membranes, and it caused an increase in the enzymatic activity. AMP‐deaminase interacted also with DOPA membranes,32 which are in a fluid state at room temperature and exerted a noncompetitive inhibition 33. This effect was observed also with other phosphatidate species containing saturated fatty acids, but only when the bilayer was in a fluid state 33…”
Section: Discussionmentioning
confidence: 87%
“…The interaction was observed with egg‐PC but not with DPPC membranes, and it caused an increase in the enzymatic activity. AMP‐deaminase interacted also with DOPA membranes,32 which are in a fluid state at room temperature and exerted a noncompetitive inhibition 33. This effect was observed also with other phosphatidate species containing saturated fatty acids, but only when the bilayer was in a fluid state 33…”
Section: Discussionmentioning
confidence: 87%
“…Phosphatidate species containing saturated fatty acids were either non-inhibitory or inhibited enzyme activity rather poorly [8]. Nevertheless, fluidization of the saturated phosphatidate species by alkalinization of the medium resulted in the appearance of an inhibitory effect of dilauroyl phosphatidate bilayers on pig heart AMP deaminase [8]. An activitory effect of PC bilayers on pig heart AMP deaminase described previously [7] involved natural egg yolk PC.…”
Section: Introductionmentioning
confidence: 84%
“…Phosphatidylcholine (PC)-containing liposomes were found to activate this enzyme in the presence of ATP [7]. On the other hand, phosphatidate bilayers composed of dioleoyl phosphatidate were found to exert non-competitive inhibition on the AMP deaminase with a K, of 15 ,uM, three orders of magnitude lower than that for orthophosphate, a well-known negative allosteric effector of AMP deaminase [8]. Another interesting finding was the established dependence of the inhibition by phosphatidate 'effectors' on membrane fluidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that the first 48 amino acids of the N-terminus of isoform E, that is highly expressed in skeletal muscle type I fibers [ 41 ], dramatically suppress contractile protein binding capacity of this enzyme [ 69 ], a behavior that could facilitate other intracellular interactions. More recently, a series of studies has shown that interactions between purified pig heart AMPD, the porcine ortholog of human isoform E [ 72 ], and isolated cytoplasmic membrane vesicles and artificial lipid bilayers [ 73 , 74 , 75 ], alters secondary structure and regulatory behavior of the enzyme. The association of the N-terminal domain of AMPD3 with the cytoplasmic face of erythrocyte ghost membranes is accompanied by reduced catalytic activity of the enzyme [ 27 ].…”
Section: A Highly Differentiated N-terminal Region Of Ampd Is Prodmentioning
confidence: 99%